Diaspora Hadrami di Nusantara - Burhanudin, Jajat (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
The development of Hadrami society, or overseas Arab communities in general, in the Indian Ocean countries have attracted some scholars to study in more detail,especially some aspects concerning the way the Hadramis live and cope with various problems they have in their overseas countries. In the Malay-Indonesia state, the Hadrami society have developed as a vital community group having important position for beyond their traditional role as